An equivalent boundary model for effects of adjacent spans on wind reliability of wood utility poles in overhead distribution lines. (1st December 2016) - Mohammadi Darestani, Yousef; Shafieezadeh, Abdollah; DesRoches, Reginald
Highlights: Effects of adjacent spans on the wind performance of utility poles are investigated. An equivalent boundary model using stiffness and force components is developed. A simplified yet accurate model is derived for the wind-induced shape of conductors. Reliability of poles in a line is assessed considering variation in poles age. Boundaries appear to have large impacts for none negligible variations in poles age. Abstract: Overhead distribution lines in the United States are primarily supported by wood poles. These utility poles are vulnerable to high wind loads from hurricanes which has resulted in a large number of power outages during past hurricanes, especially in coastal areas. Risk management of distribution systems requires development of distribution line models to reliably assess their performance under hurricanes. However, modeling the entire distribution line is not practically feasible as they are very long and consist of a large number of spans. The present study proposes analytical models to capture boundary effects of adjacent spans on the wind response of the pole of interest via equivalent springs and wind-induced forces. The stiffness of conductors (cables) is derived through a simplified solution that considers the shape of the conductors under lateral static gust wind and gravity loadings; this model is shown to be very accurate when compared to the exact analytical as well as Finite Element solutions. Deterministic and probabilistic studies are performed to assess the impact of boundary conditions on the performance of the poles; results indicate that pole boundaries may have a considerable impact on the estimates of failure probabilities especially when the extent of difference in the properties of adjacent spans is not negligible. Specifically, neglecting boundary effects from neighboring spans may result in underestimation of failure probabilities of stronger poles and overestimation of failure probabilities of weaker poles as load sharing effects among the poles are not considered. The proposed boundary model enables more reliable hurricane risk assessment of power distribution systems to effectively manage the risk of outages.